PerkembanganWilayahDiSekitarKawasanKakiJembatanSuramaduSisiMadura - , Safita Meridian; , Prof. Ir. Bambang Hari Wibisono, MUP., M.Sc., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Suramadu bridge is the bridge that crosses the Strait of Madura, which officially began its operations on June 10, 2009. The Suramadu bridge gives a great impact on the development of the region at Bangkalan Regencyin general and Suramadu Bridge Foot Area and the surrounding areas in particular. This study aims to show that regional growth occurs at the Suramadu Bridge Foot Area on Madura side, and both according to the existing condition and in terms of planning, are described in the specific objectives: (1) To describe the physical changes, social and economic development in the study area